Consequences of Climate Change for agriculture and nature in the Netherlands - Arends, Jeroen (Journal of Economic Development, Environment and People, 2012)
After the publication of the IPCC reports on climate change, the Dutch Meteorological Institute of the Netherlands (KNMI) conducted a study on the consequences of climate change for the Netherlands. Four different scenarios regarding the rise in temperature and their consequences have been developed. Other institutes have elaborated more on these scenarios, making predictions on the effects of climate change on nature and agriculture for the Netherlands. Overall conclusions are that climate change will have dramatic consequences for nature, agriculture and Dutch society in general, being so exposed to rising sea levels. Depending on the scenario, consequences have various gradients of impacts and effects. In general, it is estimated that winters will be softer and wetter, and that summers will be hotter and drier with intermittent torrential rains that can have dire consequences for agriculture and nature. Growing seasons will start earlier and will last longer which could lead to mismatches in species interaction. Species of various kind will suffer the effects of climate change and will disappear from the Netherlands altogether, either through extinction or by moving away north. Other warmth loving species from the south of the Netherlands will move upwards towards the country leading to possible threats to indigenous species.